2019
DOI: 10.3390/agronomy9110758
|View full text |Cite
|
Sign up to set email alerts
|

Soil Amendment with Biochar Affects Water Drainage and Nutrient Losses by Leaching: Experimental Evidence under Field-Grown Conditions

Abstract: Leaching of soluble elements from cultivated soils is a major concern to meet the target of agricultural sustainability in most areas. The effect of biochar application to a cultivated soil on water drainage and the consequent solute losses was assessed during a trial carried out over two consecutive growing seasons. Biochar was added to a loam-texture soil, at 0, 1, and 2% d.w. rates. A lysimeter-like set-up arranged in the experimental field-unit, allowed collecting the percolating water. Two multiple linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…On the contrary, biochar addition to the soil reduced NO 3 − content in Swiss chard leaves, likely due to the occurrence of a nitrate sorption on biochar surface. Several authors showed that biochar is effective in retaining nitrates in the soil [60][61][62][63][64][65] and attributed this ability to the high pyrolysis temperature (>600 • C) at which the biochar is obtained [66]. According to the literature, the biochar nitrate retention we hypothesized in our experiment could be explained considering the high temperature (650 • C) applied to vine pruning residues for biochar production.…”
Section: Total Nitrogen and Nitrate Leaf Contentmentioning
confidence: 60%
“…On the contrary, biochar addition to the soil reduced NO 3 − content in Swiss chard leaves, likely due to the occurrence of a nitrate sorption on biochar surface. Several authors showed that biochar is effective in retaining nitrates in the soil [60][61][62][63][64][65] and attributed this ability to the high pyrolysis temperature (>600 • C) at which the biochar is obtained [66]. According to the literature, the biochar nitrate retention we hypothesized in our experiment could be explained considering the high temperature (650 • C) applied to vine pruning residues for biochar production.…”
Section: Total Nitrogen and Nitrate Leaf Contentmentioning
confidence: 60%
“…Biochar is a carbon-rich, solid material obtained by biomass (manure, sewage sludge, wood biomass and crop residues) pyrolysis in an oxygen-limited environment [18][19][20][21]. The effects of their addition to agricultural soils depend on a number of factors, including feedstock properties and processing conditions, application rate, soil type, environmental conditions, and crop species [22,23]. About the latter, the yield response to compost or biochar applications are often contrasting; generally, either positive or negative and sometimes also neutral effects on crop yield and quality have been reported [13,24].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, biochar addition to the soil reduced NO3 -content in Swiss chard leaves, likely due to the occurrence of a nitrate sorption on biochar surface. Several authors showed that biochar is effective in retaining nitrates in the soil [60][61][62][63][64][65] and attributed this ability to the high pyrolysis temperature (>600°C) at which the biochar is obtained [66]. According to the literature, the biochar nitrate retention we hypothisez in our experiment could be explained considering the high temperature (650°C) applied to vine pruning residues for biochar production.…”
Section: Total Nitrogen and Nitrate Leaf Contentmentioning
confidence: 53%